Pharmacokinetic interactions and tolerability of rosuvastatin and ezetimibe: an open-label, randomized, multiple-dose, crossover study in healthy male volunteers - Kim H; Choi HY; Kim YH; Bae KS; Jung J; Son H; Lim HS (Dove Medical Press, 2018)
Hyungsub Kim,1 Hee Youn Choi,1 Yo-Han Kim,1 Kyun-Seop Bae,1 Jina Jung,2 Hankil Son,2 Hyeong-Seok Lim1 1Department of Clinical Pharmacology and Therapeutics, Asan Medical Center, University of Ulsan, Seoul, Republic of Korea; 2Clinical Research Team, Hanmi Pharmaceutical Co. Ltd., Seoul, Republic of Korea Purpose: Rosuvastatin is a synthetic 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor that effectively reduces low-density lipoprotein cholesterol levels. However, statin monotherapy does not always achieve acceptable low-density lipoprotein cholesterol levels in patients with severe hypercholesterolemia. Ezetimibe, a selective cholesterol-absorption inhibitor, is approved for use as a monotherapy or combination therapy with 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors for patients with hypercholesterolemia. The aim of this study was to examine the pharmacokinetics (PKs) of drug interactions between rosuvastatin and ezetimibe, and the tolerability of combined administration in healthy Korean male volunteers.Subjects and methods: Healthy subjects (n=24) were randomly allocated to 3 treatment groups: rosuvastatin (20 mg) alone, ezetimibe (10 mg) alone, and rosuvastatin (20 mg) plus ezetimibe (10 mg). The drugs were taken once every 24 hours over a period of 10 days. Blood samples were collected to analyze steady-state PKs.Results: All adverse events observed during the study were mild, and the frequency was no higher for combined administration than for mono administration. For rosuvastatin, the steady-state mean ratios (90% CI) of the combined over the single dose were 1.076 (1.019–1.136) for AUCτ,ss and 1.099 (1.003–1.204) for concentration at steady-state, respectively. In the case of free and total ezetimibe, the steady-state ratios of AUCτ,ss and concentration at steady-state were 1.131 (1.051–1.218) and 1.182 (1.038–1.346), and 1.055 (0.969–1.148) and 0.996 (0.873–1.135), respectively.Conclusion: Combined administration of rosuvastatin and ezetimibe was well tolerated. No clinically significant PK interactions between rosuvastatin and ezetimibe were observed when the 2 drugs were administered concomitantly. Keywords: rosuvastatin, ezetimibe, pharmacokinetics, DDI, tolerability